THE USEFULL OF WASTE OF MUSHROOMS FOR WORM SOIL PRODUCTION - Evi Kurniati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
In order to support conservation programs and activities, in 2011 the National Park Meru Betiri undertake community development activities by forming productive business in the form of oyster mushroom cultivation is coordinated by the Center for Rural Forestry Extension. Curahnongko village, Jember, East Java formed four groups of oyster mushroom cultivation with technology that is still traditional and opportunities to be developed. Obstacles faced by oyster mushroom cultivation is on the low efficiency of the process of watering, temperature and humidity measurement processes and packaging oyster mushrooms. In addition, baglog waste thrown away by a group of oyster mushroom cultivation due to the limited knowledge and the ability to tap into other products, among others as compost and media for the cultivation of earthworms. Through this activity, carried out innovations over technology in oyster mushroom cultivation, such as water pumps mechanical, thermometer and hygrometer, vacuum sealer for packaging of oyster mushrooms and cages permanently to the cultivation of earthworms measuring 3 x 8 x 2 m3 according to the land already owned by SMEs. The hope will be able to improve productivity and increase production of oyster mushrooms and earthworms so that the market expansion of both quality and quantity can be achieved maximum. The results of the implementation of activities is mentoring about production systems oyster mushrooms and earthworms with maximum quality results. When this has been achieved for the physical infrastructure and the provision of seeds for cultivation worms. Monitoring and evaluation of the successful implementation of activity internally and externally conducted periodically to evaluate the success of the implementation of the facility so that production equipment will have an impact on the cultivation of oyster mushrooms and earthworms